Influence of the precipitation pattern on the water runoff dynamics from the loess gully in the Lublin Upland (Eastern Poland) in the years 2003–2022 - Janicki, Grzegorz; Rodzik, Jan; Stępniewski, Krzysztof; Kociuba, Waldemar (Quaestiones Geographicae, 2025)
Over the period 2003–2022, the precipitation and runoff of water from the loess catchment with an area of 1.23 km2 was monitored. The agricultural catchment, located in Kolonia Celejów (Nałęczów Plateau, SE Poland), is drained episodically, sometimes periodically. It is dissected by a gully system with a density of erosion forms of about 6 km ∙ km−2 and it is representative for the loess areas with high gully density. The study aimed to determine the relationship between the precipitation pattern and gully water runoff. In the 20-year measurement series, four multi-year periods with similar annual hydro-meteorological indicators were distinguished. The first four years (2003–2006) predominately of snowmelt runoff, were separated as the nival period. This was followed by a short stable period in 2007–2009, with almost no gully runoff. The next period, the longest (2010–2018), was characterised by relatively mild winters and moderate snowmelt, while numerous summer rainstorms occurred. These mainly generated frequent runoff and surface wash, separating this period as pluvial. The most recent period (2019–2022), variable, was dominated by medium runoff years, with a changing dominant type. However, the contribution of propluvial and pronivial runoff in the gully was found to equalise on a multi-year scale. The observed decrease in the snowiness of winters and lack of intense snowmelt may change these proportions, in favour of propluvial runoff.